Sedimentation impacts on the growth rates of the scleractinian coral acropora formosa from fringing reefs of Tioman Island, Malaysia - R., Nakajima; T., Yoshida; Y., Fuchinove; T., Okashita; T., Maekawa; M.R.M. Kushairi,; B.H.R. Othman,; T., Toda (Universiti Kebangsaan Malaysia, 2013)
The rates of sedimentation and growth of the branching coral Acropora formosa at Marine Park, Tulai and Renggis reefs in Tioman Island, Malaysia were surveyed between November 2000 and October 2001. The sedimentation rates were measured using sediment traps and the coral growth rates were measured using digital photography and computer image analysis. The rates of sedimentation at Marine Park (17.3 ± 18.7 mg dry weight cm-2 d-1) were 5.0 times higher than the Tulai site and 11.4 times higher than the Renggis site. In contrast, both the linear extension (3.9 ± 0.9 mm month-1) and areal growth rates (3.9 ± 1.7 cm2 month-1) of A. formosa at Marine Park were significantly less than at Tulai and Renggis. The higher sedimentation and consequent lowered light levels at Marine Park may have resulted in the lower growth of the Acropora corals.